Efektivitas Penggunaan Bahan Ajar Angiospermae Berbasis Etnobotani Untuk Meningkatkan Hasil Belajar Dan Sikap Ilmiah - Siti Sunariyati; Yula Miranda; Aminah Aminah (Fakultas Keguruan dan Ilmu Pendidikan Universitas Sebelas Maret, 2020)
Teaching material is a collection of learning information needed by teachers and students in carrying out teaching and learning activities in class. Teaching materials in the form of printed books by utilizing the local potential of Angiosperms plants in the environment around students are not yet available at school. The purpose of this study was to determine the effectiveness of using Angiosperms materials based on ethnobotany in order to improve student learning outcomes and scientific attitudes. The teaching material development uses Hannafin and Peck's models. The study was conducted at Kurun High School 1. Sources of research data came from experts as validators, students as users of teaching materials and teachers as assessors of teaching materials. This research approach uses a mixed methods approach which is a mixture of qualitative and quantitative. Data were analyzed quantitatively and qualitatively. To see the effectiveness of teaching materials using an instrument in the form of a questionnaire assessed by validators, teachers and students. Then analyzed based on the percentage of ideals. Meanwhile, to find out the increase in student learning outcomes and scientific attitudes using N-gain. The results showed that Angiosperms material based on ethnobotany that were assessed by 2 expert validators and the students' responses showed that the teaching materials developed were of very good quality. Evaluation of biology teachers on teaching materials that have good categories and are suitable for use. The use of teaching materials developed has proven to be effective in improving student learning outcomes with the acquisition of N-gain in small-scale trials of 0.62 and large-scale trials of 0.53 in the medium category. It also can improve students' scientific attitudes by obtaining N-gain in small scale trials that is 0.53 and large scale trials that is 0.58 in the medium category